Religion, politics and science education in Pakistan: Analysis of Islamisation of science textbooks in tribal districts - Jan, Qasim (HTS teologiese studies, 2023)
Historically, education has largely been used for political gains and to strengthen positions of power. Similarly, ruling elites in Pakistan achieve their political interests by using education as a tool. This study problematised the religious content in the secondary school science textbooks of the national curriculum. This was illustrated in the context of the post-conflict scenario of 11 September 2001 (9/11) in the newly merged tribal districts of Khyber Pakhtunkhwa, Pakistan. A thematic analysis of the content of the science textbooks (physics and biology) was used to develop the findings of this study. This was supported by field data gathered from students’ experiences and interactions with the sample textbooks. By incorporating Foucault’s concept of the ‘regime of truth’ and Talbani’s conceptualisation of Islamisation, the study found the use of the Qur’anic verses in the sampled textbooks to be influential ‘technologies of power and self’ to Islamise science and scientify Islam to prove it as a scientific religion. In addition, it makes education increasingly irrelevant to changing socio-economic realities and aspirations among students.Contribution: The study can contribute both to theory and practice. By Islamising science education and instilling obscurantism in textbooks for schools, there is a substantial sociopolitical impact, as well as a negative impact on students’ critical thinking skills. The policymakers and actors in the Pakistani education system should therefore pay close attention to this issue. Unless the current educational system is changed, a number of generations will experience stunted growth that will be nearly impossible to reverse in the future.